Consideration of consumer priorities at expenditure of domestic enterprises on external food markets - Strashynska, Larysa; Strashynskyi, Volodymyr (My University, 2018)
The article is devoted to the definition of the essence of the “value” of the product for the consumer, the study of domestic consumer trends at the food market. The consumption of the main types of food products by the population of Ukraine is analyzed according to rational consumption norms and the level of consumption in the EU countries. It is noted that the general economic crisis in Ukraine, the reduction of purchasing power of the population, increase of prices, growth of expenses in the structure of expenditures of households (utilities, transport, etc.) without parallel increase of incomes in the coming years will not improve the situation and will not lead to increase of consumer demand at the domestic market. Moreover, current realities indicate that domestic consumers in the near future will limit their own food costs, using discounts and promotions, as well as give preference to low-priced segment products. It is determined that these tendencies force domestic enterprises to increasingly reorient their activities to foreign markets, trying to convince foreign consumers of their own competitive advantages. Over the past years, domestic producers have significantly strengthened their position at this market with regard to the export of their own products, which contributed to the preservation of added value within the country. The article outlines the main consumer trends in the development of world food markets, identifies the main priorities in the functioning of domestic enterprises when entering the external markets, existing problems and justifies the ways of their solution. It is noted that the technologies of food and beverage production vary according to global and regional trends. The “Clean label”, taste, and useful properties of the product are just a few trends that stimulate innovative developments in the food industry over the past decade. In order to meet the demands of consumers, manufacturers must keep pace with the time, understanding each new trend and its significance in different regions. Taking these trends into account will allow Ukraine to realize export opportunities and become an active player at the world food market not as a supplier of raw materials, but products with high added value. Стаття присвячена визначенню сутності цінності продукту для споживача, дослідженню вітчизняних споживчих тенденцій на ринку харчових продуктів. Проаналізовано споживання населенням України основних видів продуктів харчування відповідно до раціональних норм споживання та до рівня споживання в країнах ЄС. З’ясовано, що загальна економічна криза в Україні, зниження купівельної спроможності населення, підвищення цін, зростання витрат у структурі витрат домогосподарств (комунальні послуги, транспорт тощо) без паралельного зростання доходів у найближчі роки не покращить ситуацію і не призведе до підвищення споживчого попиту на внутрішньому ринку. Більше того, сучасні реалії свідчать, що вітчизняні споживачі в найближчій перспективі будуть обмежувати власні витрати на харчування, користуючись знижками й промоакціями, а також віддавати перевагу товарам низького цінового сегменту. Визначено, що зазначені тенденції змушують вітчизняні підприємства все більше переорієнтовувати свою діяльність на зовнішні ринки, намагаючись переконати зарубіжних споживачів у наявності власних конкурентних переваг. Протягом останніх років вітчизняні товаровиробники помітно зміцнили свої позиції на цьому ринку, що сприяло збереженню доданої вартості всередині країни. У статті окреслено основні споживчі тенденції розвитку світових продовольчих ринків, визначено пріоритети у функціонуванні вітчизняних підприємств при виході на зовнішні ринки, існуючі проблеми та обґрунтовано шляхи їх вирішення. Зазначено, що технології виробництва харчових продуктів і напоїв змінюються залежно від глобальних і регіональних тенденцій. « Чиста» етикетка, смакові якості, корисні властивості продукту — це лише декілька тенденцій, які стимулюють інноваційні розробки в галузі виробництва харчових продуктів за останні десятиріччя. Для того, щоб задовольнити запити споживачів, виробники повинні йти в ногу з часом, розуміючи кожну нову тенденцію та її значення в різних регіонах. Врахування зазначених тенденцій дасть змогу Україні реалізувати експортні можливості та стати активним гравцем на світовому ринку продовольства не як постачальник сировинних ресурсів, а продукції з високою доданою вартістю.
Keywords: food market; consumer priorities; organic agriculture; ecologically pure products; healthy food industry; “clean” label; functional product; taste properties; кафедра маркетингу; ринок продовольства; споживчі пріоритети; екологічно чиста продукція; індустрія здорового харчування; «чиста» етикетка; функціональні продукти